2021
DOI: 10.1155/2021/8859996
|View full text |Cite
|
Sign up to set email alerts
|

Potential Prognostic Biomarkers of Lung Adenocarcinoma Based on Bioinformatic Analysis

Abstract: Lung adenocarcinoma (LUAD), which accounts for 60% of non-small-cell lung cancers, is poorly diagnosed and has a low average 5-year survival rate (approximately 20%). It remains the leading cause of cancer-related deaths worldwide. Studies on long noncoding RNAs (lncRNAs) in LUAD-related competing endogenous RNA (ceRNA) networks are limited. We aimed to identify novel prognostic biomarkers for LUAD using bioinformatic tools and data analysis. We systemically integrated differentially expressed genes and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…The results in Supplementary Figure S3 showed that FMR1-IT1 and PTOV1-AS2 can be detected in clinical diagnosis. AF131215.5 is one of lncRNAs in lung adenocarcinoma (LUAD)-related competing endogenous RNA networks, and showed an independent prognostic value of overall survival for patients with LUAD ( Hou and Yao, 2021 ). FMR1 intronic transcript 1 (FMR1-IT1) is also known as FMR1 intronic transcript 1 (non-protein coding) or Fragile X Mental Retardation Syndrome Protein (FMRP) or FMR1, there were evidence that FMRP regulated tumor invasiveness-related pathways in melanoma cells by impacting cell migration, invasion and adhesion ( Zalfa et al, 2017 ), and its overexpression was associated with lung metastasis of murine breast cancer ( Lucá et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results in Supplementary Figure S3 showed that FMR1-IT1 and PTOV1-AS2 can be detected in clinical diagnosis. AF131215.5 is one of lncRNAs in lung adenocarcinoma (LUAD)-related competing endogenous RNA networks, and showed an independent prognostic value of overall survival for patients with LUAD ( Hou and Yao, 2021 ). FMR1 intronic transcript 1 (FMR1-IT1) is also known as FMR1 intronic transcript 1 (non-protein coding) or Fragile X Mental Retardation Syndrome Protein (FMRP) or FMR1, there were evidence that FMRP regulated tumor invasiveness-related pathways in melanoma cells by impacting cell migration, invasion and adhesion ( Zalfa et al, 2017 ), and its overexpression was associated with lung metastasis of murine breast cancer ( Lucá et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the nine GI-lncRNAs used for construction of the GI-lncRNA model, the biological functions of FAM83A (Wang et al, 2020;Zeng et al, 2020). Although the biological functions of AF131215.5 and RHOXF1-AS1 have not been reported in cancer, our results are in accordance with previous findings showing that these two lncRNAs are associated with the OS of LUAC (Hou and Yao, 2021). The remaining five lncRNAs have not been reported in lung cancer or other human cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Six NETs-related lncRNAs (AF131215.5, MYOSLID, NKILA, AC090152.1, SNHG10, and TRG.AS) have been reported to be associated with cancer progression. AF131215.5 was found to have an independent prognostic value of overall survival for patients with lung adenocarcinoma (LUAD) [ 24 ]. In terms of partial epithelial-mesenchymal transition (p-EMT), MYOSLID expression in head and neck squamous cell carcinoma (HNSCC) was closely correlated with Slug, PDPN, and LAMB3, and is a key regulator of tumor cell survival.…”
Section: Discussionmentioning
confidence: 99%